Testing the Level Organoleptics for Moringa (Moringa oleifera) Biscuits with the Addition of Tuna (Thunnus Sp) Bone Flour as an Additional Food for Children Toddlers - Tingginehe, Rosmin Mariati; Halim, Anissa (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the 2030 SDG targets, namely SDG target 2, the Indonesian government has attempted to provide interventions to reduce stunting rates, both specific interventions and sensitive interventions. One of the government's efforts is to provide functional food in the form of high-calorie biscuits to stunted toddlers. Several obstacles often occur, one of which is distribution where the PMT biscuits are produced outside Papua and it takes time for distribution until when they arrive in the community the biscuits have expired and cannot be consumed. Organoleptic test results for color preference levels, panelists liked Moringa Biscuits with the addition of 20% tuna bone meal; for the level of preference for aroma, panelists liked Moringa Biscuits with the addition of 10% tuna bone meal; for taste preference level, panelists liked Moringa Biscuits with the addition of 30% tuna fish bone meal; For the level of preference for texture, panelists liked Moringa Biscuits with the addition of 20% tuna bone meal.